2016
DOI: 10.3109/13880209.2015.1137602
|View full text |Cite
|
Sign up to set email alerts
|

Sedative effect of central administration ofCoriandrum sativumessential oil and its major component linalool in neonatal chicks

Abstract: Context Coriandrum sativum L. (Apiaceae) (coriander) is an herb grown throughout the world as a culinary, medicinal or essential crop. In traditional medicine, it is used for the relief of anxiety and insomnia. Systemic hydro-alcoholic and aqueous extract from aerial parts and seeds had anxiolytic and sedative action in rodents, but little is known about its central effect in chicks. Objective To study the effects of intracerebroventricular administration of essential oil from coriander seeds and its major com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 33 publications
2
15
0
2
Order By: Relevance
“…While α-pinene, β-pinene, δ-3-carene and limonene are widespread among wood species, the emission of linalool from construction materials has never been reported. Studies have illustrated the anxiolytic, memory-enhancing and neuroprotective effect of coriander essential oil upon inhalation and have attributed this to the presence of linalool (Cioanca et al, 2013;Emamghoreishi et al, 2005;Gastón et al, 2016). Further, numerous reports have described antibacterial and antifungal activity against a wide range of micro-organisms (Elgayyar et al, 2001), while Silva et al (2011) have stressed the significance of the S-(+)-enantiomer of linalool, which predominance was confirmed in this study, for the inhibitory activity against Gram negative bacteria including important food pathogens.…”
Section: Voc Emissions From Self-bonded Coriander Boardssupporting
confidence: 73%
“…While α-pinene, β-pinene, δ-3-carene and limonene are widespread among wood species, the emission of linalool from construction materials has never been reported. Studies have illustrated the anxiolytic, memory-enhancing and neuroprotective effect of coriander essential oil upon inhalation and have attributed this to the presence of linalool (Cioanca et al, 2013;Emamghoreishi et al, 2005;Gastón et al, 2016). Further, numerous reports have described antibacterial and antifungal activity against a wide range of micro-organisms (Elgayyar et al, 2001), while Silva et al (2011) have stressed the significance of the S-(+)-enantiomer of linalool, which predominance was confirmed in this study, for the inhibitory activity against Gram negative bacteria including important food pathogens.…”
Section: Voc Emissions From Self-bonded Coriander Boardssupporting
confidence: 73%
“…Similarly, it has been previously reported that EO from coriander seeds induce a sedative effect in chickens (Gastón et al. ).…”
Section: Discussionsupporting
confidence: 60%
“…LI is the main volatile monoterpene compound found in several aromatic plants, such as Lavandula angustifolia Mill., Rosmarinus officinalis L. and Coriandrum sativum L. (Kuroda et al, 2005;Batista et al, 2010;Gastón et al, 2016). In a previous study, LI significantly improved the cognitive performance and alleviated Ab 1-40 -induced cell injury by increasing the levels of oxidative stress indicators such as SOD, GPX, and AChE.…”
Section: Linalool (Li)mentioning
confidence: 93%